Case reportEctopia cordis and amniotic band syndrome - Pamidi, Narendra; Vollala, Venkata R.; Nayak, Satheesha; Bhat, Seetharama (Archives of Medical Science, 2008)
Amniotic band syndrome is a collection of fetal malformations associated with fibrous bands that appear to entangle or entrap various fetal parts in utero leading to deformation, malformation, or disruption. Ectopia cordis is a rare congenital defect in fusion of the anterior chest wall resulting in extrathoracic location of the heart. In this article, we report a rare case of ectopia cordis and amniotic band syndrome in a 26-week-old female fetus. The congenital deformities observed in the present case may be due to earlier rupture of the amnion, ossification defects in bones of the skull, or maternal illness.